تفعيل دور المحاسبة الإدارية في مناهج الكلفة ,الزبون ,المنافس باستخدام انموذج المنطق المضبب - د. قاسم محسن الحبيطي (PROSPECTIVE RESEARCHES, 2023)
The present paper displays the effective ways which activize the role of accountancy to meet the increased demands of administration to cope with the surrounding developments. One of these ways is to give accountancy a strategic role to interact with the environment besides the internal atmosphere. Thus, what so-called strategic administrative accountancy has appeared. The foggy logical model is used as an approach to deal with that strategic role by interacting with administration strategies such as cost guiding and excellence strategy provided that this should take place through certain strategies like cost, costumer, and competitor. The preliminary treatment has shown that its results may be adopted by administrative accountant in the processes of high tightening the strategic decision making by which a set of variables could be invested.